2012
DOI: 10.1186/1471-2407-12-226
|View full text |Cite
|
Sign up to set email alerts
|

Experimental in vivo and in vitro treatment with a new histone deacetylase inhibitor belinostat inhibits the growth of pancreatic cancer

Abstract: BackgroundTreatment options for pancreatic ductal adenocarcinoma (PDAC) are limited. Histone deacetylase inhibitors are a new and promising drug family with strong anticancer activity. The aim of this study was to examine the efficacy of in vitro and in vivo treatment with the novel pan-HDAC inhibitor belinostat on the growth of human PDAC cells.MethodsThe proliferation of tumour cell lines (T3M4, AsPC-1 and Panc-1) was determined using an MTT assay. Apoptosis was analysed using flow cytometry. Furthermore, p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 28 publications
3
29
0
1
Order By: Relevance
“…It should be stated that all reported in vitro studies have a different time-regime, i.e., our long-term study is more aligned with the time-frame of animal experiments 2,11,14,17,23,55,78,79,95 ( Fig. 7) and clinical trials, 56,58,69,73,105,106 pointing to the great potential of our scaffold in providing a reproducible, low cost powerful tool for replacing animals in long-term realistic treatment screening for PDAC.…”
Section: Assessment Of Combination Of Chemotherapy and Radiotherapy Imentioning
confidence: 83%
See 3 more Smart Citations
“…It should be stated that all reported in vitro studies have a different time-regime, i.e., our long-term study is more aligned with the time-frame of animal experiments 2,11,14,17,23,55,78,79,95 ( Fig. 7) and clinical trials, 56,58,69,73,105,106 pointing to the great potential of our scaffold in providing a reproducible, low cost powerful tool for replacing animals in long-term realistic treatment screening for PDAC.…”
Section: Assessment Of Combination Of Chemotherapy and Radiotherapy Imentioning
confidence: 83%
“…6 More specically, the socalled tumour microenvironment (TME), which is a cocktail of biochemical, cellular, biomechanical and structural components has been shown to affect the efficiency of treatment delivery to the tumour. 4,[7][8][9] Traditionally, PDAC research including treatment screening, is conducted in (a) 2D in vitro systems [10][11][12][13] (tissue culture asks or Petri-plates) or in (b) animals, mainly mice. 10,11,[14][15][16][17][18] Generally, 2D in vitro cultures are responsive to radiotherapy and chemotherapy, reproducible and very easy to use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed synergistic antiproliferative and proapoptotic effects of the two drugs in pancreatic cancer cell lines [72]. More recently, two studies showed that belinostat induces growth inhibition, in vitro and in vivo in immunodeficient mice, alone or synergistically with gemcitabine [73,74].…”
Section: Hydroxamic Acidsmentioning
confidence: 99%